The management pattern and outcomes of chronic thromboembolic pulmonary hypertension: rationale and design for a Chinese real-world study - Shuai Zhang; Yishan Li; Yuanhua Yang; Sugang Gong; Zhenwen Yang; Cheng Hong; Xiaopei Cui; Jun Wan; Yingqun Ji; Hong Chen; Ling Zhu; Chenghong Li; et al. (BMC Pulmonary Medicine, 2024)
Abstract Background Chronic thromboembolic pulmonary hypertension (CTEPH) is a progressive pulmonary vascular disorder with substantial morbidity and mortality, also a disease underdiagnosed and undertreated. It is potentially curable by pulmonary endarterectomy (PEA) in patients with surgically accessible thrombi. Balloon pulmonary angioplasty (BPA) and targeted medical therapy are options for patients with distal lesions or persistent/recurrent pulmonary hypertension after PEA. There is an urgent need to increase the awareness of CTEPH. Qualified CTEPH centers are still quite limited. Baseline characteristics, management pattern and clinical outcome of CTEPH in China needs to be reported. Methods and design The CHinese reAl-world study to iNvestigate the manaGEment pattern and outcomes of chronic thromboembolic pulmonary hypertension (CHANGE) study is designed to provide the multimodality treatment pattern and clinical outcomes of CTEPH in China. Consecutive patients who are ≥ 14 year-old and diagnosed with CTEPH are enrolled. The diagnosis of CTEPH is confirmed in right heart catheterization and imaging examinations. The multimodality therapeutic strategy, which consists of PEA, BPA and targeted medical therapy, is made by a multidisciplinary team. The blood sample and tissue from PEA are stored in the central biobank for further research. The patients receive regular follow-up every 3 or 6 months for at least 3 years. The primary outcomes include all-cause mortality and changes in functional and hemodynamic parameters from baseline. The secondary outcomes include the proportion of patients experiencing lung transplantation, the proportion of patients experiencing heart and lung transplantation, and changes in health-related quality of life. Up to 31 December 2023, the study has enrolled 1500 eligible patients from 18 expert centers. Conclusions As a real-world study, the CHANGE study is expected to increase our understanding of CTEPH, and to fill the gap between guidelines and the clinical practice in the diagnosis, assessment and treatment of patients with CTEPH. Registration Number in ClinicalTrials.gov NCT05311072.